Avaliação in vitro da rugosidade superficial e manutenção dos selantes de superfícies para resinas compostas submetidos à escovação - Bonatto, Fernanda (2013)
Objectives : 1) to evaluate the roughness of three surface sealants applied on a composite resin when subjected to simulated toothbrushing for different periods, 2) to evaluate, with the aid of scanning electron microscopy, the presence of surface sealants after simulated toothbrushing; 3) evaluating whether the type of dentifrice may shorten the life of the sealing surface. Materials and Methods : One hundred and eight bodies of the specimens were fabricated with resin Amelogen Plus, divided into 6 groups (n = 18) according to the type of surface sealant (Fortify (F), BisCover LV (B) and Permaseal (P)) and toothpaste (Colgate Total 12 Clean Mint (CT) and Colgate Total Professional Whitening 12 (PW)). The samples were subjected to brushing cycles, simulating periods of 6 months, 12 months, 18 months and 24 months. After each period, the samples had a surface roughness measured. An additional group of 48 samples was conducted for SEM analysis. The results were analyzed by ANOVA with three fixed factors (sealants, time and toothpaste) and Tukey's test (α = 5%). Results : BisCover had the lowest average surface roughness (0.06 μm) compared with sealants Fortify (0.09 μm) and Permaseal (0.08 μm), which were not statistically different. The Fortify on 12 months of brushing, had the highest average roughness (0.13 μm). The average roughness for the dentifrice CT was lower (0.07 μm), compared to the PW (0.08 μm) and was statistically different. The roughness increased up to 12 months of simulated brushing (0.04 μm, 0.08 μm and 0.11 μm), decreasing at the 18th month (0.08 μm) up to 24 months of brushing (0.07 μm). Conclusions : The sealant Fortify had the highest average roughness in 12 months of simulated toothbrushing, and the lowest roughness values were obtained by BisCover. Through SEM, it was observed that none of the seals used in the study was completely removed from the resin by 24 months of brushing.